Managing Knowledge of Stakeholders’ Interests towards Sustainable Development - Krisnawati, Astrie (Journal of Social and Development Sciences, 2013)
This study aims to find a linkage between Knowledge Management and Sustainable Development through implementation of Triple Bottom Line concept. It is a conceptual paper that applies literature review for proposing a conceptual model as the finding of this study. The model describes how a company should manage the knowledge to maintain good relationships with all of its stakeholders in order to achieve sustainable development in creating mutual benefit value for the good of all parties. This study identifies who the company’s stakeholders are, what their interests, and what knowledge the company should have and manage to fulfill the stakeholders’ interests towards sustainability. The conceptual model needs to be examined empirically. A case study implementing this model into a certain company can be considered as the further research.